Complete response under sorafenib in patients with hepatocellular carcinoma: Relationship with dermatologic adverse events. Issue 2 (2nd January 2018) - Rimola, Jordi; Díaz‐González, Álvaro; Darnell, Anna; Varela, María; Pons, Fernando; Hernandez‐Guerra, Manuel; Delgado, Manuel; Castroagudin, Javier; Matilla, Ana; Sangro, Bruno; Rodriguez de Lope, Carlos; Sala, Margarita; et al.
Abstract : The clinical benefit of sorafenib in patients with hepatocellular carcinoma (HCC) has been undervalued due to the absence of complete responses, even though patients who develop early dermatologic reactions have shown to have a positive outcome. In addition, sorafenib is described as an antiangiogenic drug, but it also acts on immunological cells. Thus, the goal of this study was to assess the complete response rate in a retrospective cohort of HCC patients treated with sorafenib and to describe the profile of the patients who achieve complete response for identifying factors related to this event and their connection with the immunological profile of sorafenib. Ten Spanish centers submitted cases of complete response under sorafenib. The baseline characteristics, development of early dermatologic reactions, and cause of treatment discontinuation were annotated. Radiological images taken before starting sorafenib, at first control, after starting sorafenib, at the time of complete response, and at least 1 month after treatment were centrally reviewed. Of the 1119 patients studied, 20 had been classified as complete responders by the centers, but eight of these patients were excluded after central review. Ten patients had complete disappearance of all tumor sites, and two had just a small residual fibrotic scar. Thus, 12 patients were classified as complete responders (58% HCV, median age 59.7 years, 83.4% Child‐Pugh class A, Eastern Cooperative Oncology Group performance status 0 91.7%, and Barcelona Clinic Liver Cancer stage C 83.3%). The median overall survival and treatment duration were 85.8 and 40.1 months, respectively. All but one patient developed early dermatologic reactions, and seven patients discontinued sorafenib after achieving complete response due to adverse events, patient decision, or liver decompensation. Conclusion : Complete response affects 1% of patients with HCC who are treated with sorafenib. The association of complete response with early dermatologic reactions supports the role of a specific immune/inflammatory patient profile in the improved response to sorafenib. (Hepatology 2018;67:612‐622).